Self-templating hydrothermal synthesis of carbon-confined double-shelled Ni/NiO hollow microspheres for diphenylamine detection in fruit samples - Sakthivel, Rajalakshmi; He, Jr-Hau; Chung, Ren-Jei (Journal of hazardous materials, 2022)
Toxic substances, such as heavy metals, toxins, pesticides, pathogens, and veterinary drug residues in food are hazardous to consumer health. The variety and quantity of food consumption have increased owing to developments in the agricultural and food industries. Food safety has a substantial socioeconomic impact, and an increasing number of consumers have become aware of its importance. Therefore, simple and cost-effective analytical methods are required to quantify the safety of preservatives. Herein, we report an electrochemical method using double-shelled carbon-confined Ni/NiO (C@Ni/NiO) hollow microspheres to detect diphenylamine (DPA). The microspheres were synthesized by a self-templating hydrothermal method followed by calcination. The hydrothermal temperature and precursor ratio were optimized systematically to prepare double-shelled C@Ni/NiO hollow microspheres. The excellent electrocatalytic activity and electron transport properties of a C@Ni/NiO-modified glassy carbon electrode (GCE) were exploited in the electrochemical oxidation of DPA. Interestingly, the engineered C@Ni/NiO/GCE has a wide dynamic linear range (0.02–473 μM) and a DPA detection limit of 0.007 μM. In addition, the DPA sensor exhibited good selectivity, reproducibility, repeatability, and stability. The practical feasibility of the DPA sensor was evaluated in fruit samples (sweet tomatoes, apples, and red grapes), with considerable recovery. [Display omitted] •Double-shell structured C@Ni/NiO is synthesized by a self-templating method.•Sucrose-derived carbon enhances the conductivity also converts the NiO to metallic Ni.•The C@Ni/NiO modified GCE was applied for the electrocatalytic oxidation of DPA.•The practical feasibility of the DPA sensor was evaluated in fruit samples.•The C@Ni/NiO preparation and fabrication process is simple and cost-effective.